Propagation model for cellular mobile networks used in UAVcommunications environmentss - Silvério, André de Sousa (2017)
Recognizing the growth of the drone market in recent years, it is crucial to evaluate the capacity of the mobile communications technologies as well as their infrastructure to verify if these are capable to support various applications and services that may associate with these type of vehicles, achieving lower costs to the users. The type of application chosen for this thesis is a video streaming that is able to assume different qualities depending on the RF conditions, in order to overcome the limitation of radio communications, in which the user is only able to communicate with the drone when in his line of sight. It was necessary to take into account a propagation model that considered the unique characteristics of an UAV, since the most commonly used models only consider a typical mobile user moving below the level of the BSs and their respective antennas using a short/medium frequency interval that is not able to consider the third and fourth generation technologies at once. In order to choose the ideal model, a theoretical study was carried out, which allowed to conclude that Lisbon University Institute Model is the most accurate since it is able to fulfill the requirements associated to a flying drone, considering a larger frequency spectrum, allowing the use of third and fourth generation technologies that are fundamental to support multimedia services, such as video streaming. To verify the viability of mobile communications, measurements were made in three real scenarios in rural areas using a spectrum analyzer carried by a flying drone, in order to monitor, read and write the data related to the signal’s behavior into a file, during the flight route. Based on this approach, it was possible to analyze the viability of mobile communications for a video streaming service using a drone, in a rural environment and considering UMTS and LTE technologies. In addition, evaluate the signal’s performance when the drone is above the antennas where the “hole phenomenon” occurs, theoretically.